2015
DOI: 10.1590/s1677-5538.ibju.2014.0209
|View full text |Cite
|
Sign up to set email alerts
|

Transobturator Midurethral Slings versus Single-Incision Slings for Stress Incontinence in Overweight Patients

Abstract: Purpose:To compare transobturator midurethral sling (TOS) and single-incision sling procedures in terms of their effects on urinary incontinence and the quality of life in overweight (BMI ≥25-29.9 kg/m2) female patients using the International Consultation on Incontinence Questionnaire scoring form (ICIQ-SF) and Quality of Life of Persons with Urinary Incontinence scoring form (I-QOL).Materials and Methods:In this prospective trial, the patients were divided into two groups consecutively; first 20 overweight f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…The etiology seems to be the stronger support seen in the urethra in this surgical method. 8 In our study, no significant difference in urodynamic parameters was observed between the two studied techniques.…”
Section: Discussioncontrasting
confidence: 46%
“…The etiology seems to be the stronger support seen in the urethra in this surgical method. 8 In our study, no significant difference in urodynamic parameters was observed between the two studied techniques.…”
Section: Discussioncontrasting
confidence: 46%
“…[ 11 12 13 ] Although TOT is nowadays being offered as treatment of choice in many centers as it is an effective method of treatment of SUI, reports have indicated varying success rates for the procedure. [ 14 15 16 ] In the current study, the TOT was very successful as all the patients were relieved of their symptoms and the patients did not demonstrate incontinence at follow-up. However, at 5-year follow-up two patients had Grade I urinary incontinence for which they declined any further evaluation and were offered Kegels exercises.…”
Section: Discussionmentioning
confidence: 54%
“…Developing measurement tools for the Malay version of the I-QoL is crucial as there is no valid Malay-language questionnaire to measure the QoL of people with UI symptom. The English version of the I-QoL has been widely used by researchers to measure QoL among people with UI and has been translated and validated in more than 16 languages ( 25 , 30 32 ). However, there has been no validation study on the I-QoL in Malay using a confirmatory approach.…”
Section: Discussionmentioning
confidence: 99%